TRANSFORMASI DIGITAL DALAM PEMBELAJARAN MUSIK: STUDI BIBLIOMETRIK BERBASIS SCOPUS (2020–2025) - Firdaus; Firman; Zulfahmi, Muhammad; Alfalah; Halim, M. (Information Technology Education Department, 2026)
This study aims to map the development of research on digital transformation in music learning through a bibliometric approach based on Scopus data for the 2020–2025 period. The analysis was conducted to identify publication trends, thematic structure, and geographic distribution of research. The method used was bibliometrics with the help of VOSviewer to analyze keyword co-occurrence, thematic clusters, and the interrelationships between key concepts within the study area. The results show that publication trends fluctuated at the beginning of the period, then increased significantly in the later years, indicating a process of normalization and strengthening of the role of digital technology in music education. The thematic structure shows the dominance of pedagogical concepts such as music education and e-learning, but is beginning to evolve towards more complex technologies such as artificial intelligence and immersive systems. Meanwhile, the geographic distribution shows a dominance of developed countries with limited involvement from developing countries. The conclusion of this study confirms that digital transformation in music learning is an ongoing process of educational paradigm evolution, with a developmental direction toward more adaptive, inclusive, and multidisciplinary technology integration within the modern music learning ecosystem. Keywords: Digital Transformation; Music Learning; Bibliometrics; Digital Music Education.